2017
DOI: 10.1007/s10637-016-0416-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability and pharmacokinetics of the fibroblast growth factor receptor inhibitor AZD4547 in Japanese patients with advanced solid tumours: a Phase I study

Abstract: Summary Background AZD4547 is a potent, oral, highly selective fibroblast growth factor receptor (FGFR) inhibitor in clinical development for treating tumours with a range of FGFR aberrations, including FGFR mutations, amplifications and fusions. Methods This open-label, Phase I, multicentre study (NCT01213160) evaluated the safety, pharmacokinetics, and preliminary antitumour efficacy (RECIST v1.1) of AZD4547 monotherapy in Japanese patients with advanced solid tumours. Part A was a dose-escalation part; Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…Reasons for TEAE‐related dose interruptions included nausea (n = 3), vomiting (n = 2), anorexia (n = 2), nasopharyngitis (n = 1), and decreased neutrophil count (n = 1). Selective FGFR inhibition has been associated with an increased risk of hyperphosphatemia and eye toxicity, including retinal detachment . In the present study, there were nine AE of hyperphosphatemia and three AE of retinal detachment, but all were <grade 3 in severity and did not lead to dose reduction or discontinuation.…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…Reasons for TEAE‐related dose interruptions included nausea (n = 3), vomiting (n = 2), anorexia (n = 2), nasopharyngitis (n = 1), and decreased neutrophil count (n = 1). Selective FGFR inhibition has been associated with an increased risk of hyperphosphatemia and eye toxicity, including retinal detachment . In the present study, there were nine AE of hyperphosphatemia and three AE of retinal detachment, but all were <grade 3 in severity and did not lead to dose reduction or discontinuation.…”
Section: Resultsmentioning
confidence: 46%
“…FGFR signaling is involved in the regulation of FGF23 expression, and increased FGF23 production has been implicated in the development of several hypophosphatemic diseases . Selective FGFR inhibitors are typically associated with on‐target toxicities such as hyperphosphatemia, which appears to play a role in FGF23 signaling and eye toxicity such as macular edema and retinal detachment, as reported previously . No clear relationship between these toxicities and the inhibition of FGFR has been found.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Compounds 11-28 were prepared with a similar procedure as that used for 8. [2,3-b] [2,3-b]pyrazine (11) [2,3-b]pyrazine (14). [2,3-b]pyrazine (15) [2,3-b]pyrazine (16) [2,3-b]pyrazine (17 [2,3-b]pyrazine (18 …”
Section: Chemistrymentioning
confidence: 99%
“…Aberrant FGFR signaling could be caused by different mechanisms, including activating mutations in FGFRs, oncogenic fusion of FGFRs and over-expression of FGFRs [10]. Currently, several FGFR-targeted agents, mostly are small molecules binding to the kinase domain, are evaluated in clinical trials for cancer treatment, and most intriguing and advanced evaluated are FGFR-selective inhibitors, such as AZD4547 (1) [11], NVP-BGJ398 (2) [12] and JNJ-42756493 (3) [13]. As investigated by Patani et al [14], due to the landscape of activated mutations in FGFR kinases, the above-mentioned FGFR inhibitors (1, 2, 3) showed distinct effects towards different mutants, which indicated that developing FGFR inhibitors with novel scaffold are highly demanded as they may provide unique therapeutic benefits towards certain patients.…”
Section: Introductionmentioning
confidence: 99%